Cervical cancer prevention in Libya-public awareness, barriers to screening and the attitudes of health care professionals / Nada Ab. Mansour Hweissa - Nada, Ab. Mansour Hweissa (2018)
The age-standardized incidence rate of cervical cancer in Libya is 4.8 per 100,000. Free screening is only available for women who are at high risk or exhibit one or more symptoms and who have been recommended by healthcare providers. Asymptomatic women need to go to private healthcare facilities and pay out of pocket for regular screening. A cross-sectional survey was carried out in Az-Zawiya city to explore the population‟s awareness of cervical cancer, their willingness to pay for screening tests and the anticipated delay in help seeking. A total of 412 face-to-face interviews were conducted, using Arabic version of the Cervical Cancer Awareness Measure questionnaire and willingness to pay questions. Descriptive statistical analysis was performed to assess the socio-demographic characteristics of the respondents and their awareness of cervical cancer. Then, Analysis of variances was done to identify socio-demographic variances in the knowledge score on the warning signs and risk factors of cervical cancer. The logistic regression was performed to identify socio-demographic variations in the willingness to pay for cervical cancer screening. Moreover, a binary logistic regression was conducted on anticipated delay in help seeking. Furthermore, qualitative studies based on in-depth interviews were done to assess the healthcare providers‟ attitude towards and recommendation practices for cervical cancer screening. The other qualitative study was based on focus group discussions held with women from Az-Zawiya city to define the perceived barriers toward cervical cancer screening practice. Both qualitative studies were analysed using thematic analysis. The study revealed the existence of socio-demographic variation in awareness of both warning iv signs and risk factors. Knowledge scores of cervical cancer symptoms and risk factors were higher in women who were aged 30–39 years, were married, had obtained a higher education qualification and earned a higher income. In addition, 54.6% of the respondents indicated that they would seek for help within two weeks if there were any warning signs of cervical cancer. Women who had mentioned that they would not delay were more likely to be younger than 40 years, married and have higher socio-economic status. Furthermore, only 37.9% indicated that they would be willing to pay for a regular screening test. The in-depth interviews explored the reasons for the lack of recommendations being given by providers of Libyan healthcare facilities to women on the need for them to have a cervical cancer screening test. The results highlight the role played by healthcare professionals in motivating women to attend cervical cancer screening programmes. Healthcare providers stressed the necessity for implementation of a reminder system for cervical cancer screening and the awareness campaigns about cervical cancer screening. Finally, numerous barriers preventing women from undertaking a Pap smear test were identified; lack of knowledge, financial constraints and accessibility to screening services being the main ones. The study offers some suggestions to the authorities to improve health education as it is essential to maximize public awareness of cervical cancer prevention. Firstly, more information on cervical cancer and screening should be disseminated through educational and awareness campaigns. Secondly, healthcare providers should play an important role in providing clearer information about cervical cancer and the benefits of screening. As a conclusion, the awareness of cervical cancer symptoms and risk factors among women from the city Az-Zawiya in Libya was low. Suggestions are made to the respective authorities to improve existing health education programme, which is essential to maximise public awareness of cervical cancer prevention. In addition, more information on cervical cancer and its screening should be disseminated through educational and awareness v campaigns. Moreover, health care providers should play an important role to provide clearer information about cervical cancer and the benefits of its screening. There is also a promising possibility to increase the cervical cancer screening rate by implementing low cost or free organized population based screening programme.